Effect of different diets on the fatty acid compo- sition of buffalo bulk milk - Sebastiana Failla; Giuliano Palocci; Michela Contò; Gianluca Renzi; Chiara Evangelista; Loredana Basiricò; Umberto Bernabucci (Revista Científica)
Feed can affect the fatty acids (FA) composition of buffalo milk. Therefore, diet could improve the nutritional value of buffalo milk such as increasing polyunsaturated fatty acids n-3 (PUFA n-3), and conjugated linoleic acid (CLA), with high nutritional value for humans. The study aimed to evaluate the effect of diets and seasons on buffalo milk fatty acid composition. During a year, 120 samples of bulk buffalo milk were taken from ten farms. Animals were fed with ten different isoenergetic and isoproteic diets. They were provided as a total mixed ratio where different components (about 3% in dry matter of total ration) were added to the essential diet for each group: basic diet (B) was composed of maize silages, alfalfa hay, corn grain, and soybean as concentrates, the second diet contained linseed as an additional constituent to B (L), another brewer’s spent grain (T), additional alfalfa and mixed hay (H), additional corn grain (M), grass (G); other farms included in B diet both grass and cottonseed (CG), grass and linseed (GL) or grass and brewer’s spent grain (TG) and at last grass linseed and brewer’s spent grain (LTG). Fatty acids in buffalo milk were quantified after extraction and methylation by GC/ FID. Data were analyzed by a bi-factorial model with interaction (season x diet) using GLM procedure and the statement “contrast” by SAS Software to highlight the effect of the constituents of diets. Compared to the others, seasonal effects were evident in milk FA, mainly for spring and summer, with an increase in saturated fatty acids (SFA) and a decrease in PUFA of about 10%. Linseed diets (L, LG, LTG) showed an increase (p<0.001) of PUFA n-3 (0.63 vs. 0.38 g/100g of fat) compared with the others. While milk from the CG and TG diets showed an increase (p<0.001) in PUFA n-6, the differences were also evident in the n6/n3 ratio (3.1 vs. 5.2, p<0.001). Diets T and M showed an increase (p<0.002) in SFA and a decrease p<0.001 in CLA (-20%). Instead, the G diet allowed a higher (p<0.0004) content of CLA (0.90 vs 0.74 g/100g of fat), highlighting the positive contribution of grass on ruminal activity. Instead, the addition of linseed and cottonseed to the G diet caused a decrease (p<0.001) in CLA and branch fatty acids due to the excessive presence of PUFA. The feeds supplied attend all metabolic pathways, and in particular, linseed and grass could enrich the milk with nutraceuticals. However, the right balance must be found between the constituents to maximize their positive contribution.